Quality of life after functional endoscopic sinus surgery - Begh, Raies Ahmad; Saraf, Aditiya; Kishore, Kamal; Kalsotra, Parmod (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: This paper aims to assess improvement in quality of life (QOL) after functional endoscopic sinus surgery through questionnaire sino-nasal outcome test (SNOT)-22. Methods: The present study was conducted on 50 patients in Department of ENT and HNS, SMGS Hospital, GMC Jammu during a time period of July 2017 to September 2019. All the patients with age ≥18 years who failed to respond to medical therapy (3 months) and underwent functional endoscopic sinus surgery (FESS) were included in the study. SNOT-22 questionnaire was used to assess the improvement. Results: In our study, preoperative SNOT scores were higher (54±8.05) but after FESS they reduced significantly at 1st (16.47±5.51), 3rd (13.86±4.19), 6th months (12.9±8.05) post operatively. Chronic rhinosinusitis (CRS) with nasal polyposis group had greater mean difference of SNOT-22 scores (43.93) between preoperative period and 3 months postoperative period than patients grouped as CRS without nasal polyposis (41.47). Conclusions: We concluded that FESS is the best surgical intervention for chronic rhinosinusitis. It significantly improves the quality of life of patients of chronic rhinosinusitis.